Potential of Chlorogenic Acid from Coffea canephora to Improving Innate Immunity System Components among BALB / c Mice - Christina Destri1, Jusak Nugraha2, Muhammad Amin3, Djoko Agus Purwanto4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this study was to verify the phagocytosis activity which displayed in CD11b and B220 markersand also the markers of erythroid 2 nuclear factor related factor 2 (Nrf2) as a key regulatory transcriptionfactor on various antioxidant gene expressions and Superoxide dismutase (SOD) as an antioxidant markerthat related with protein. Nrf2 plays an important role to inhibit the ROS accumulation and eliminate freeradicals. The active compound of chlorogenic acid in robusta coffee type (Coffea canephora) in IndonesianCoffee and Cocoa Research Center was used in three groups of mice in this study and it was gave differentdose in each groups. The assessment samples were taken from the peritoneal fluid of mice than it wasanalyzed by using Flow Cytometry method to find phagocytosis function and antioxidant activity. Theresults of ANOVA statistical test was p <0.05 in all parameters, this mean that there was indicated that theactive compound of chlorogenic acid in coffee was involved in natural immune system mechanism and itwas seen in increasing of phagocytic activity and antioxidant levels.